Design Of A Semi-Automatic Bread-Making Machine Including Medium Capacity With A Variety Of Baking Temperatures - Leyn, Hermanus Bey Leyn Bey; Riyadi, Slamet; Siswadi, Siswadi; Khusna, Dwi; Muharom, Muharom; Nugroho, Wahyu; Nugroho, Alfi (Journal of System Engineering and Technological Innovation, 2023)
The bread machine is also a leverage to increase production capacity and production quality. In contrast to manual bread production, which requires a lot of effort and time, a bread machine makes everything more efficient. The bread machine's output is better than manual production's. Besides that, the hygiene of the bread produced is guaranteed. The device is sterile and safe because all materials are protected with stainless plates, a mixer motor flame that can be adjusted according to needs, and an automatic oven according to requirements. The tray uses hygienic, not harmful to health, and environmentally friendly and pollution-free materials. The level of safety in use is higher because it has appropriate dimensions. The technique for operating a semi-automatic bread-making machine with a production capacity of 4 kg requires 45 minutes with an oven process temperature of 100 ºC to 150 ºC.